Getting Rid of 1 over a Variable

Jason76

Senior Member
Joined
Oct 19, 2012
Messages
1,180
I know you can cross-multiply on this one. But let's say we're going a different route (which this is good to know for problems for "1 over a variable" where you can't cross multiply):

\(\displaystyle \dfrac{50}{5} = \dfrac{40}{y}\)

\(\displaystyle \dfrac{50}{40(5)} = \dfrac{1}{y}\) - Take reciprocal of both sides to get rid of "1 over y"

\(\displaystyle \dfrac{40(5)}{50} = y\)

\(\displaystyle \dfrac{40(5)}{50} = y\)

\(\displaystyle 4 = y\)

But what if

\(\displaystyle \dfrac{-50}{5} = \dfrac{40}{y}\)

\(\displaystyle \dfrac{-50}{40(5)} = \dfrac{1}{y}\) - :confused: If you take the reciprocal of both sides, then does the negative sign on the 50 change?

\(\displaystyle \dfrac{40(5)}{-50} = y\)

\(\displaystyle \dfrac{40(5)}{-50} = y\)

\(\displaystyle -4 = y\)
 
Last edited:
Sure you can : 1/a = 2/b ; 1*b = 2*a

You can criss cross multiply also for "a variable over 1":
a/1 = 2/b ; a*b = 1*2

Sure, but in some cases we want an equation in the form: "\(\displaystyle y =\) other part of function". Not "\(\displaystyle \dfrac{1}{y} =\) other part of function". Some situations it's impossible to get it in the right form using crisscross multiplying. Am I wrong?
 
I can't imagine a situation where you can "take the reciprocal of both sides" but can't "cross multiply". Can you give an example?
 
Sure, but in some cases we want an equation in the form: "\(\displaystyle y =\) other part of function". Not "\(\displaystyle \dfrac{1}{y} =\) other part of function". Some situations it's impossible to get it in the right form using crisscross multiplying. Am I wrong? YES, you are wrong.
\(\displaystyle \dfrac{a}{b} = \dfrac{c}{d} \implies\)

\(\displaystyle b * \dfrac{a}{b} = b * \dfrac{c}{d} \implies\)

\(\displaystyle a = \dfrac{bc}{d} \implies\)

\(\displaystyle a * d = \dfrac{bc}{d} * d \implies\)

\(\displaystyle ad = bc.\)

In short, \(\displaystyle \dfrac{a}{b} = \dfrac{c}{d} \implies ad = bc.\)

\(\displaystyle However,\ it\ is\ false\ that\ ad = bc \implies \dfrac{a}{b} = \dfrac{c}{d}.\)

The latter proposition may be what you are thinking about.
 
Some situations it's impossible to get it in the right form using crisscross multiplying. Am I wrong?

I'm not sure what you may be thinking, here. For example, are you thinking that one ought to be able to get the desired form in a single step, by using cross-multiplication? That's not always the case.

I'd like to see the situation(s) which you have in mind. :cool:
 
Top